Pengaruh Gaya Kepemimpinan, Lingkungan Kerja, dan Stres Kerja terhadap Kinerja Pegawai (Studi Kasus Perum BULOG Kantor Cabang Malang) - Safitri, Dessy; Singgih, Muhamad Nur (University of Merdeka Malang, 2022)
Advances in existing information technology make companies required to be able to further develop human resources in the company. To support the improvement of employee performance, having a leadership style is very important for a leader. as a result of this, it is necessary to create comfort in the work environment. This research is intended to analyze the influence of leadership style, work environment and work stress on employee performance. The sample in this study was 40 respondents. The sampling technique in this study used a saturated sampling technique. Data collection was carried out online using a google form where there was a questionnaire that was distributed to respondents. Data analysis uses classical assumption tests, multiple linear regression analysis, coefficient of determination tests, hypothesis tests, t tests, and f tests. The results of the analysis show that leadership style, work environment, and work stress have a significant positive effect on employee performance.